COVID-19 surveillance in educational institution as an early detection in subpopulation - Hargono, Arief; Martini, Santi; Hidajah, Atik Choirul; Astutik, Erni (Intelektual Pustaka Media Utama, 2023)
Since the first time it was discovered in 2019, COVID-19 has been the major threat to public health. Surveillance is considered to be one of the main pillars in dealing with the pandemic as it enhances the efforts of prevention and control of COVID-19. This study aimed to develop COVID-19 surveillance system at Universitas Airlangga that play a great importance in detecting and monitoring of COVID-19 status among its academias. This study refers to system approach which include system analysis and system design. System analysis was conducted by describing it into its components, namely input, process, and output. The results from system analysis are then utilized to the system design. The surveillance system collects and analyzes data which resulted to epidemiological information and recommendation. The result from the monitoring then utilized as an effort to enhance the coordination for epidemic preparedness in the institution. This study concludes that the COVID-19 surveillance system model in this institution monitors the COVID-19 status and associated risk factors of the sub-population within the institution. The information generated is used by decision-makers for early detection and monitoring of COVID-19 status.